Nanozyme-loaded colorimetric gelatin methacryloyl microneedles for glucose detection in interstitial fluid - Shixian Lin; Ziqing Mao; Mengyao Miao; Wensheng Lin; Min Hu; Xinyan Shi; Ruxi Jin; Xiaoyu Lv; Ruijie Liang; Shijie Wang; Jingyan Li; Yupeng Xie; et al. (Analytica Chimica Acta, 2026)

Divergent responses of soil methanogens and methanotrophs to climatic warming in a Tibetan alpine meadow - Yigang Hu; Saipeng Hou; Yuzhang Li; Zhenhua Zhang; Xingwu Lin; Liang Jiao (Applied Soil Ecology, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Effects of ecological restoration on soil organic carbon in degraded sloping cropland: An 8-year resampling study - Meiying Wang; Honghong Lin; Xingwu Duan (Agriculture, Ecosystems & Environment, 2026)

Successional trajectories differ between soil microbial guilds after logging in mixed conifer-broadleaf forests - Qiuyan Tan; Xingwu Lin; Leho Tedersoo; Jiasui Li; Xiuhai Zhao; Jianguo Zhu; Haiyan Chu; Teng Yang (Plant and Soil, 2025)

Decade-long successive biochar amendment enhances wheat production and increases crop system resistance to unfavorable meteorological factors - Zhe Chen; Penghui Jin; Qi Liu; Yanhui Zhang; Tianlong Hu; Hui Wang; Rong Zhou; Jingru Zhang; Xingwu Lin; Zubin Xie (Field Crops Research, 2025)

Biological nitrogen fixation in paddy soils is driven by multiple edaphic factors and available phosphorus is the greatest contributor - Tianlong HU; Yanhui ZHANG; Hui WANG; Haiyang JIN; Benjuan LIU; Zhibin LIN; Jing MA; Xiaojie WANG; Qi LIU; Hongtao LIU; Zhe CHEN; Rong ZHOU; et al. (Pedosphere, 2024)

Composted maize straw under fungi inoculation reduces soil N2O emissions and mitigates the microbial N limitation in a wheat upland - Rong Zhou; Hui Wang; Jingru Zhang; Zhe Chen; Penghui Jin; Tianlong Hu; Qing Bian; Xingwu Lin; Xueqiang Zhao; Zubin Xie (Science of The Total Environment, 2024)

12-year continuous biochar application: Mitigating reactive nitrogen loss in paddy fields but without rice yield enhancement - Penghui Jin; Zhe Chen; Hui Wang; Runjin Lv; Tianlong Hu; Rong Zhou; Jingru Zhang; Xingwu Lin; Qi Liu; Zubin Xie (Agriculture, Ecosystems & Environment, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

Biochar application increases biological nitrogen fixation in soybean with improved soil properties in an Ultisol - Xingwu Lin; Zubin Xie; Tianlong Hu; Hui Wang; Zhe Chen; Rong Zhou; Penghui Jin (Journal of Soil Science and Plant Nutrition, 2023)

Responses of soil water-holding capacity to environmental changes in alpine ecosystems across the southern Tibetan Plateau in the past 35–40 years - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Li Rong; Jiangcheng Huang (CATENA, 2023)

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

Experimental Warming Increases Seasonal Methane Uptake in an Alpine Meadow on the Tibetan Plateau - Xingwu Lin; Shiping Wang; Yigang Hu; Caiyun Luo; Zhenhua Zhang; Haishan Niu; Zubin Xie (Ecosystems, 2015)

Effect of warming and grazing on litter mass loss and temperature sensitivity of litter and dung mass loss on the Tibetan plateau - CAIYUN LUO; GUANGPING XU; ZENGGUO CHAO; SHIPING WANG; XINGWU LIN; YIGANG HU; ZHENHUA ZHANG; JICHUANG DUAN; XIAOFENG CHANG; AILING SU; YINGNIAN LI; XINQUAN ZHAO; et al. (Global Change Biology, 2010)
Knowledge about the role of litter and dung decomposition in nutrient cycling and response to climate change and grazing in alpine ecosystems is still rudimentary. We conducted two separate studies to assess the relative role of warming and grazing on litter mass loss and on the temperature sensitivity of litter and dung mass loss. Experiments were conducted for 1–2 years under a controlled warming–grazing system and along an elevation gradient from 3200 to 3800 m. A free‐air temperature enhancement system (FATE) using infrared heaters and grazing significantly increased soil temperatures (average 0.5–1.6 °C) from 0 to 40 cm depth, but neither warming nor grazing affected soil moisture except early in the growing seasons at 30 cm soil depth. Heaters caused greater soil warming at night‐time compared with daytime, but grazing resulted in greater soil warming during daytime compared with night‐time. Annual average values of the soil temperature at 5 cm were 3.2, 2.4 and 0.3 °C at 3200, 3600 and 3800 m, respectively. Neither warming nor grazing caused changes of litter quality for the first year of the controlled warming–grazing experiment. The effects of warming and grazing on litter mass losses were additive, increasing litter mass losses by about 19.3% and 8.3%, respectively, for the 2‐year decomposition periods. The temperature sensitivity of litter mass losses was approximately 11% °C −1 based on the controlled warming–grazing experiment. The annual cumulative litter mass loss was approximately 2.5 times that of dung along the elevation gradient. However, the temperature sensitivity (about 18% °C −1 ) of the dung mass loss was about three times that of the litter mass loss. These results suggest greater warming at night‐time compared with daytime may accelerate litter mass loss, and grazing will enhance carbon loss to atmosphere in the region through a decrease of litter biomass and an increase of dung production with an increase of stocking rate in future warmer conditions.

Infrared heater arrays for warming ecosystem field plots - BRUCE A. KIMBALL; MATTHEW M. CONLEY; SHIPING WANG; XINGWU LIN; CAIYUN LUO; JACK MORGAN; DAVID SMITH (Global Change Biology, 2008)
There is a need for methodology to warm open‐field plots in order to study the likely effects of global warming on ecosystems in the future. Herein, we describe the development of arrays of more powerful and efficient infrared heaters with ceramic heating elements. By tilting the heaters at 45° from horizontal and combining six of them in a hexagonal array, good uniformity of warming was achieved across 3‐m‐diameter plots. Moreover, there do not appear to be obstacles (other than financial) to scaling to larger plots. The efficiency [ η h (%); thermal radiation out per electrical energy in] of these heaters was higher than that of the heaters used in most previous infrared heater experiments and can be described by: η h = 10 + 25exp(− 0.17 u ), where u is wind speed at 2 m height (m s − 1 ). Graphs are presented to estimate operating costs from degrees of warming, two types of plant canopy, and site windiness. Four such arrays were deployed over plots of grass at Haibei, Qinghai, China and another at Cheyenne, Wyoming, USA, along with corresponding reference plots with dummy heaters. Proportional integral derivative systems with infrared thermometers to sense canopy temperatures of the heated and reference plots were used to control the heater outputs. Over month‐long periods at both sites, about 75% of canopy temperature observations were within 0.5 °C of the set‐point temperature differences between heated and reference plots. Electrical power consumption per 3‐m‐diameter plot averaged 58 and 80 kW h day − 1 for Haibei and Cheyenne, respectively. However, the desired temperature differences were set lower at Haibei (1.2 °C daytime, 1.7 °C night) than Cheyenne (1.5 °C daytime, 3.0 °C night), and Cheyenne is a windier site. Thus, we conclude that these hexagonal arrays of ceramic infrared heaters can be a successful temperature free‐air‐controlled enhancement (T‐FACE) system for warming ecosystem field plots.